PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VISUAL TERHADAP PENCAPAIAN KRITERIA KETUNTASAN MINIMAL (KKM) SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTS. MIFTAHUL ULUM BETTET PAMEKASAN - St Rabihah; Abd Haris (Journal of Education Partner, 2023)
There are two main problems in this research, first, regarding whether or not there is an influence of the use of visual learning media on students' achievement of minimum completeness criteria (KKM) in Islamic Cultural History Subjects at MTs. Miftahul Ulum Bettet Pamekasan, secondly, how big is the influence of the use of visual learning media on students' achievement of minimum completeness criteria (KKM) in Islamic Cultural History Subjects at MTs. Miftahul Ulum Bettet Pamekasan. The aim of this research is, firstly, to determine whether or not there is an influence of the use of visual learning media on students' achievement of minimum completeness criteria (KKM) in the History of Islamic Culture subject at MTs. Miftahul Ulum Bettet Pamekasan. Second, find out how much influence the use of visual learning media has on students' achievement of minimum completeness criteria (KKM) in the History of Islamic Culture subject at MTs. Miftahul Ulum Bettet Pamekasan. This research uses a quantitative correlational approach. Meanwhile, the population in this study were female students in grades VII, VIII and IX at MTs. Miftahul Ulum Bettet Pamekasan. The research instruments used were questionnaires and documentation as the main or primary instruments, while observation and interviews were complementary or secondary. Data collection will take place for approximately 35 days starting Tuesday, June 27 2023 to July 31 2023. The data analysis technique used is statistical analysis using the product moment technique. The results of this research show that (1) There is an influence of the use of visual learning media on students' achievement of Minimum Completeness Criteria (KKM) in Islamic Cultural History Subjects at MTs. Miftahul Ulum Bettet Pamekasan, it can be seen that r work is 0.513 which is greater than the r in the product moment table at a significance of 95% 0.259 or 95% 0.330. (2) The use of visual learning media has quite an influence on students' achievement of the Minimum Completeness Criteria (KKM), this is proven by the r-work of 0.513 being in the range of 0.40 to 0.70 with a Fair interpretation.